VEGANISMO OU VEGANISMOS? TENSÕES DISCURSIVAS SOBRE CONSUMO E POLÍTICA NO MOVIMENTO VEGANO - David Arioch da Silva Alves Barcelos (2024)
This research proposes a reflection on the tense and discursive movement of the so-called contemporary vegan movement and how the dispute over the meanings of veganism is established from the perspective of consumption and politics. We evaluate this tense dispute mainly between popular veganism and pragmatic veganism. To do this, we first seek to understand the emergence and influences of veganism, as well as its specificities in Brazil. In order for such changes and discursive pluralities to emerge in the vegan movement, we rely on the assumptions of Cultural Studies, initially identifying how such discourses move and gain strength in the context of colonialism. Through dialogue with the studies of Néstor García Canclini (2015) and Jesús Martín-Barbero (2008), we understand that such discursive conflicts materialize through negotiations and mediations that, if they aim to favor the growth of veganism, also aim to favor a movement to the detriment of another. As an approximation for this analytics, we realize that with regard to consumption, movements present differences in perception and relationship with the hegemonic and that these result from differences in the perception of politics. In this way, disputes between movements also stop being just about what to consume as opposed to animal exploitation and also start to be about where to consume, since a (popular) movement, due to its anti-capitalist position, reveals a more intransigent attitude position than the other (pragmatic). We believe that such research also brings advances in thinking about conflicts in the vegan movement in relation to animal liberation more as a question of means than of ends, since the differences mainly involve the means used to bring people closer to veganism, and can serve as subsidy for other research that points to this discussion. We also conclude that the vegan movement in itself is already a movement of sociocultural mediators, considering the interest, regardless of the approach, in expanding the meanings of consumption and politics by not thinking about them only in the relationship between human beings and human beings. Based on what is presented in this research, and considering the importance of an intersectionality that is focused on other causes for veganism, such as social justice and human rights, we also propose attention to the recognition of non-human animals as excluded from consideration as oppressed by human interests through exploitation, other uses and impacts.